Return On Asset Mediating Financial Performance in Measuring Stock Return - Sofyaun*, Ashari; Juniar, Asrid; Rahmawati, Rini; Hanni, Eisa F (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The aim of this study is to find out the impact of Current Ratio, Net Profit Margin, and Debt to Equity Ratio on Return on Asset and Stock Return. The data used is a source of data that has been available both internal and external data and data can be accessed through the internet and publication of information. Data used is the financial report of the sub-sector food and beverages companies listed on the Indonesian Stock Exchange period 2018-2022. Analysis methods show that Current Ratio and Debt to Equity Ratio have no influence on Return on Asset and Stock Return. Net Profit Margin has an effect on Returns on Assets and Asset Return. Return On Assets has an influence upon Stock Return. Return on Asset cannot mediate the Current Ratio and Debt to Equity Ratio against the Stock Return. Return on Asset can mediate the Net Profit Margin against the Stock Return.